Nonlinear forecasting of stream flows using a chaotic approach and artificial neural networks (2013)
This paper evaluates the forecasting performance of two nonlinear models, k-nearest neighbor (kNN) and feed-forward neural networks (FFNN), using stream flow data of the Kızılırmak River, the longest river in Turkey. For the kNN model, the required parameters are delay time, number of nearest neigh- bors and embedding dimension. The optimal delay time was obtained with the mutual information function; the number of nearest neighbors was obtained with the optimization process that minimi- zes RMSE as a function of the neighbor number and the embedding dimension was obtained with the correlation dimension method. The correlation dimension of the Kızılırmak River was d = 2.702, which was used in forming the input structure of the FFNN. The nearest integer above the correlation dimension (i.e., 3) provided the minimal number of required variables to characterize the system, and the maximum number of required variables was obtained with the nearest integer above the value 2d + 1 (Takens, 1981) (i.e., 7). Two FFNN models were developed that incorporate 3 and 7 lagged discharge values and the predicted performance compared to that of the kNN model. The results showed that the kNN model was superior to the FFNN model in stream flow forecasting. However, as a result from the kNN model structure, the model failed in the prediction of peak values. Additionally, it was found that the correlation dimension (if it existed) could successfully be used in time series where the determina- tion of the input structure is difficult because of high inter-dependency, as in stream flow time series. ResumenEste trabajo evalúa el desempeño de pronóstico de dos modelos no lineares, de método de clasificación no paramétrico kNN y de redes neuronales con alimentación avanzada (FNNN), usando datos de flujo del río Kizilirmak, el mayor de Turquía. Para el modelo kNN, los parámetros requeridos son tiempo de retraso, número de vecindarios cercanos y dimensión de encrustamiento. El tiempo óptimo de retraso fue obtenido con la función de información mutua; el número de vecindarios cercanos fue obtenido con la optimización de procesos que minimizan el RMSE como una función del número de vecindarios y la dimensión de incrus- tación fue obtenida con el método de dimensión correlativa. La dimensión de correlación del río Kizilirmak fue utilizado en la formación de la estructura de ingreso de las redes FFNN. La integración cercana sobre la dimensión de correlación proveyó el número mínimo de variables requeridas para caracterizar el sistema y el número máximo de variables requeridas fue obtenido con el número entero por encima del valor (Takens, 1981). Se desarrollaron dos modelos de redes FNNN que incorporan 3 y 7 valores de descargas retrasadas y el desempeño de predicción comparado con el modelo kNN. Los resultados muestran que el modelo kNN fue superior al modelo de redes FFNN en el flujo de pronósticos. Sin embargo, como un resultado del modelo de estructura kNN, el modelo falla en los valores pico. Adicionalmente, se encontró que la dimensión de correla- ción (de existir) podría ser usada eficientemente en series temporales donde la determinación de estructura de ingreso es difícil por la gran interdependencia, como en las series temporales de flujo.